Biofilm recovery after treatment with an anionic and cationic surfactant at sublethal concentrations - Simões, M. (2004)
The biofilm recovery after treatment with SDS (anionic surfactant) and with CTAB (cationic surfactant) was investigated. Biofilms were formed by Pseudomonas fluorescens on stainless steel slides, under turbulent and laminar flow. The post-surfactant application effect was assessed, in terms of biofilm respiratory activity, by measuring the oxygen uptake rate, and biofilm mass, immediately after surfactant application and 3, 7 and 12 hours after each treatment. It was found that after SDS and CTAB application, the biofilms recovered its respiratory activity that in some cases reached higher values than the ones found for the control experiments. Biofilms formed under turbulent flow had a higher potential to recover their metabolic activity than biofilms formed under laminar flow when treated with SDS. The CTAB application promoted similar recovery in the respiratory activity for both biofilms. Concerning biofilm mass, any significant variation was detected. Control experiments showed that biofilms were in a metabolic steady-state.